Numerical and Experimental Analysis of Airfoil Profile (OODBODHAN, 2025)
This project presents a combined numerical and experimental analysis of the aerodynamic behavior of the NACA 0015 airfoil, focusing on lift characteristics. The experimental investigation was conducted in an open-type subsonic wind tunnel at the Institute of Engineering, Pashchimanchal Campus, with airflow velocities 9–16m/s. Numerical simulations were performed using ANSYS Fluent, applying the standard k-epsilon turbulence model across different inlet velocities. Lift forces obtained from both approaches were compared to evaluating accuracy and consistency. The results showed good agreement between experimental and CFD data, particularly at angles of attack 10° and 15°, validating the effectiveness of CFD as an alternative to experimental methods. This study enhances the understanding of flow behavior around airfoils and provides a foundation for further investigations into performance optimization in aerospace and engineering applications.